Da‘wah by Millennial Preachers on TikTok and Religious Literacy among Muslim Senior High School Students in Tunggak Cerme Village - Devi Fitriah Islamiyah; Benny Prasetiya (Green Publisher, 2026)
This study examines the phenomenon of millennial preachers (da’i milenial) on TikTok and its implications for the religious literacy of Muslim high school adolescents in Tunggak Cerme Village, Probolinggo Regency. Employing a qualitative descriptive case study approach, this research aims to deeply understand the characteristics of digital preaching, the level of religious literacy, and the process of internalizing religious messages among adolescents. The findings reveal that millennial preachers on TikTok employ egalitarian communication styles, use popular and contextual language, and present short, interactive visual content that resonates with the spiritual and psychological needs of youth. TikTok functions as an informal learning space that strengthens the cognitive, affective, and behavioral dimensions of students’ religious literacy. However, the brevity and fragmented nature of content often lead to partial understanding and limit the development of critical and moderate religious literacy. The effectiveness of such digital preaching depends heavily on the guidance of teachers, parents, and supportive religious environments. This study concludes that millennial preachers’ digital da’wah on TikTok represents a strategic innovation in contemporary Islamic propagation, with the potential to enhance youth religiosity when accompanied by strengthened digital literacy, ethical media engagement, and synergy between formal and non-formal religious education.